Effect of sinusoidally heating on mixed convection in square cavity filled with a porous medium - Zainuddin, N.; Abu Bakar, Norhaliza; Karimipour, A.; Roslan, R. (Asian Research Publishing Network (ARPN), 2017)
Unsteady mixed convection flows in a lid-driven square cavity filled with a fluid-saturated porous medium is investigated numerically. The two vertical walls of the enclosure are insulated while the bottom wall is cooled. The top wall is heated sinusoidally and moving at a constant speed. The governing equations are solved numerically by using finite volume method with SIMPLE algorithm. The results with different parameters of Darcy and Richardson numbers are obtained and shown graphically. The presence of porous medium has influence to the movement of heat transfer and fluid flow inside the cavity. While, the effect of sinusoidal heating causes the flow patterns of streamline and isotherm increase and look strength.